Evaluation of the Clinical, Laboratory, and Radiological Findings and Treatment of 19 Cases of Pancreatic Echinococcosis - Gou, Li (Open Forum Infect Dis, 2020)
BACKGROUND: Hydatid disease is a severe health problem in endemic areas. In recent years, the incidence of this disease in China has been increasing. As the imaging characteristics of pancreatic echinococcosis (PE) are similar to those of cystic diseases, such as cysts, tuberculosis, and tumors, PE is often misdiagnosed and mistreated. METHODS: The clinical manifestations, laboratory tests, radiological findings, and treatment of 19 patients with PE between January 2006 and December 2018 in 2 hospitals were retrospectively analyzed. RESULTS: The mean age of the patients was 38 years, and the ratio of women to men was 2. All patients came from rural areas. Clinical manifestations included cholestatic jaundice, mass, nausea, pain, and swelling. Hemagglutination inhibition test results were positive for all patients. Enzyme-linked immunosorbent assay test results were positive in 17 cases (89.5%). Foci in the pancreas were head in 52.6%, body in 26.3%, body and tail in 15.8%, tail in 5.3%. The size of lesions’ diameter ranged from 1 to 12 cm (mean, 6.5 cm). The imaging features of PE included the presence of (a) daughter cysts on abdominal computed tomography (CT) and/or magnetic resonance imaging (MRI); (b) internal cyst wall dissection and ribbon sign on abdominal CT and/or MRI; (c) typical eggshell cyst wall calcification on abdominal CT. CONCLUSIONS: For patients with cystic lesions on CT and/or MRI combined with epidemiological history and positive echinococcosis serology, doctors can correctly diagnose PE earlier. Surgical treatment combined with drugs can reduce the mortality of PE, leading to a better prognosis.